If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+3-6x+6-9x-9=12-12x+15x+18+27
We simplify the equation to the form, which is simple to understand
3x+3-6x+6-9x-9=12-12x+15x+18+27
We move all terms containing x to the left and all other terms to the right.
+3x-6x-9x+12x-15x=+12+18+27-3-6+9
We simplify left and right side of the equation.
-15x=+57
We divide both sides of the equation by -15 to get x.
x=-3.8
| 5/6*-1/5x+4=7/10x | | 5x-41=3x-11 | | 0=-6x-4x+5 | | .8x+.5y=6597 | | (x+5)(x-5)-x(x-1)=0 | | 10x-5x-6-10x=7 | | 3(z+9)-(6z-9)=-4z | | 10/3-5=4/3x+7 | | 8+6x-4=9x+12-7x | | 7z-7=8z | | 25+17s=76 | | x/16=-8 | | -7-3=4x+7-3x | | x/25=-20+20 | | x-12=-29 | | 8-.5Q=1Q | | 8s=-72 | | 56*23-67/98*32= | | 7202-.23Q=.46Q | | 375-.25Q=.5Q | | 5.6q-5.3-5.2q=-0.6q-1.2 | | 9x-18+36/9x | | 24-0.10Q=.20Q | | 8x-6y=-96 | | x-8=-1+3 | | 5x+67=10x-13 | | 3x-12/x-2a+4/9 | | 12x+8-5=11x-2 | | 3y+2x=10 | | 3(y+2)+y=u(y-1)+10 | | 4g=-5s | | 31-3x=6x+16 |